The Methodology of Al-Qiyas Al-Iqtirānī by ʿAbd Al-Qādir Wangah in Describing The Attribute of Qidam’s Burhān in Taqrib Al-Ikhwan - Ahmad Hafiz Ali Makdom; Mohd Hasrul Shuhari; Syed Hadzrullathfi Syed Omar; Mohammed Muneer'deen Olodo Al-Shafi'i; Mohd Shaifulbahri Abdullah (Cyber Media Indonesia, 2021)
'Abd al-Qadir Wangah is a preacher and scholar who is well known in the Malay Archipelago. His field expertise is more to Usuluddin who is the core of one's Islam. The proof, he authored several books that talk about the science of Tawhid such as Taqrīb al-Ikhwān fī Taʿallum ʿAqā’id al-Īmān, Asās al-ʿItiqād and so on. Therefore, this paper focuses on the debate on monotheism through the nature of qidam Allah SWT in addition to presenting the methodology of al-qiyās al-iqtirānī in describing the tafṣīlī evidence of the debate on that nature. This qualitative study uses the method of documentation and content analysis through the text of Taqrīb al-Ikhwān by ‘Abd al-Qādir Wangah as well as logic references such as Īḍāḥ al-Mubham, Mughni al-Ṭullāb and so on. Aspects of the debate will focus on the biography of ʿAbd al-Qādir Wangah briefly. Later, this study will include a debate on the nature of salbiyyah, especially on the nature of qidam. Next, this paper will discuss the methodology of al-qiyās al-iqtirānī specifically according to the logical scholars and its application in describing the evidence of qidam and in Taqrīb al-Ikhwān. As a result, the use of al-qiyas al-iqtirānī is applied by ʿAbd al-Qādir Wangah indirectly through two contexts of muttaṣilah verses instead of ḥamliyyah both or munfaṣilah both or one ḥamliyyah and another muttaṣilah or ḥamliyyah munfaṣilah or mutta in describing burhān the nature of qidam of Allah SWT. Abstract: ʿAbd al-Qādir Wangah seorang pendakwah dan ulama Melayu yang sangat terkenal di Nusantara. Kepakaran bidangnya lebih kepada Usuluddin yang menjadi teras agama Islam seseorang. Buktinya, beliau mengarang beberapa kitab yang membicarakan berkenaan dengan ilmu Tauhid seperti Taqrīb al-Ikhwān fī Taʿallum ʿAqā’id al-Īmān, Asās al-ʿItiqād dan sebagainya. Oleh yang demikian, makalah ini memfokuskan perbahasan tauhid menerusi sifat qidam Allah SWT di samping mengemukakan metodologi al-qiyās al-iqtirānī dalam menghuraikan dalil tafṣīlī terhadap perbahasan sifat tersebut. Kajian berbentuk kualitatif ini menggunakan kaedah dokumentasi dan analisis kandungan menerusi teks Taqrīb al-Ikhwān karya ‘Abd al-Qādir Wangah serta rujukan ilmu mantik seperti Īḍāḥ al-Mubham, Mughni al-Ṭullāb dan sebagainya. Aspek perbahasan akan tertumpu kepada biografi ʿAbd al-Qādir Wangah secara ringkas. Kemudian, kajian ini akan memuatkan perbahasan sifat salbiyyah khususnya pada sifat qidam. Seterusnya, makalah ini akan membincangkan berkenaan metodologi al-qiyās al-iqtirānī secara khusus menurut para ulama mantik dan aplikasinya pada menghuraikan dalil qidam dan baqā’ dalam Taqrīb al-Ikhwān. Hasilnya, penggunaan al-qiyas al-iqtirānī ini diaplikasikan oleh ʿAbd al-Qādir Wangah secara tidak langsung menerusi dua konteks ayat yang muttaṣilah bukannya secara ḥamliyyah kedua-duanya atau munfaṣilah kedua-duanya atau satu ḥamliyyah dan satu lagi muttaṣilah atau ḥamliyyah munfaṣilah atau muttaṣilah munfaṣilah dalam menghuraikan burhān sifat qidam Allah SWT.